Two Japanese Infants With Hypothyroidism Following Exposure to Iodinated Contrast Media. Issue 2 (17th February 2023) - Shimura, Kazuhiro; Shibata, Hironori; Hasegawa, Tomonobu; Ishii, Tomohiro
Abstract: We report 2 Japanese infants with hypothyroidism requiring levothyroxine (LT4) replacement therapy following exposure to iodinated contrast media (ICM). Patient 1 was born at 32 weeks gestation. He had congenital heart disease and underwent contrast-enhanced computed tomography (CT) on day 22 (estimated amount of iodine: 600 mg/kg/dose). The newborn mass screening showed normal thyrotropin (thyroid-stimulating hormone; TSH) levels at day 4, but high TSH and low free thyroxine levels on retest at day 44. LT4 replacement therapy was administered on days 46 to 74. No hypothyroidism requiring LT4 replacement therapy was observed afterward. The ultrasonography showed a hypoplastic thyroid gland. Patient 2 was born full-term. She had congenital heart disease and underwent contrast-enhanced CT on day 52 (estimated amount of iodine: 1500 mg/kg/dose). The newborn mass screening showed normal TSH levels on day 4, but high TSH levels on retest on day 62. LT4 replacement therapy was administered from day 65 to 3 years of age. Genetic analysis showed a heterozygous variant of DUOX2 . Exposure to ICM can result in hypothyroidism, requiring LT4 replacement therapy. The severity of hypothyroidism may depend on risk factors, such as genetic predisposition, preterm birth, thyroid hypoplasia, or early exposure to ICM.